Pharmacological Potential of the Stem of Butterfly Root Plant (Phanera semibifida Roxb. var. semibifida): A Phytochemical, Toxicity, and Anti-Inflammatory Activity Study - Ayu Mellyanti; Rita Hairani; Erwin Erwin; Winni Astuti; Medi Hendra; Eva Marliana (Sam Ratulangi University, 2025)
Phanera semibifida Roxb. var. semibifida, commonly known as the butterfly root plant, is one of the plants frequently used by various indigenous tribes in Kalimantan as a traditional medicinal plant. This study was conducted to identify the secondary metabolite compounds, toxicity level, and anti-inflammatory activity of the plant. Extraction of the stem of the butterfly root plant was carried out using the maceration method with methanol as the solvent, followed by partitioning with n-hexane and ethyl acetate. Phytochemical screening of the stem was performed using Thin Layer Chromatography (TLC). Toxicity testing was conducted using the Brine Shrimp Lethality Test (BSLT), and anti-inflammatory activity was evaluated based on protein denaturation inhibition in vitro using a ultraviolet-visible (UV-Vis) spectrophotometer. The crude extract of the stem was found to contain alkaloids, triterpenoids, steroids, flavonoids, and phenolics; the n-hexane fraction contained triterpenoids and steroids; the ethyl acetate fraction contained alkaloids, triterpenoids, steroids, flavonoids, and phenolics, while the aqueous fraction contained alkaloids, flavonoids, and phenolics. The toxicity levels (LC₅₀) of the crude extract, n-hexane fraction, ethyl acetate fraction, and aqueous fraction were 57.45; 158.04; 42.34; and 72.88 µg/mL, respectively, indicating toxic activity against Artemia salina L. larvae. The anti-inflammatory activity levels (IC₅₀) of the crude extract, n-hexane fraction, ethyl acetate fraction, and aqueous fraction were 124.95 µg/mL (moderate category); 161.27 µg/mL (moderate category); 99.15 µg/mL (strong category); and 143.44 µg/mL (moderate category), respectively. These results indicate that the stem of the butterfly root plant (Phanera semibifida Roxb. var. semibifida) contains bioactive compounds and has potential as a natural anti-inflammatory agent.